Electrochemical Characterization of Mass Transport at Microelectrode Arrays - Torres Hernández, Walter (Revista de Ciencias, 2014)
Electrodes with dimensions in the micro- and nano-meter scale can be used as analytical probes in confi ned places such as cells and organelles. Arrays of microelectrodes, particularly disk-shaped electrodes, are now a platform to fabricate electrochemical sensors and multisensors. A useful characteristic of such arrays is that enhancement of the current signal is due to the fact that radial diffusion becomes important as the disk radius gets smaller and steady state currents are attainable in a relatively short time. Because there is no general analytical solution for the current response at MEAs, previous characterization of any micro electrode array at hand is still required. This paper discusses the electrochemical characterization of the mass transport of a reversible electrochemical probe at a commercially available micro-disk electrode array by two commonly used tools for electro analysis, namely: cyclic voltammetry and chronoamperometry. The questions to be addressed are whether clear radial diffusion control can be effectively achieved and the time required for the electrode system to reach steady state. For chronoamperometric experiments, the current response almost achieves steady state in the time range between 0.49 s and 1 s. This is precisely the time bracket in which analytical measurements should be made in order to achieve high sensitivity.